Pica and attention deficit hyperactivity disorder: is there a link? Comorbidity and treatment outcomes with methylphenidate - Cardoso,Daniela (2021)
Abstract Introduction: Pica is the persistent ingestion of non-nutritive substances. It is common during childhood and may be related to nutritional deficits, intellectual disability, stress, and psychosis. However, no causative biological condition is identified in most cases and there is limited evidence to support pharmacological intervention. As several authors describe pica as an impulse control disorder and impulsive symptoms are a core aspect of the diagnostic criteria of attention deficit hyperactivity disorder (ADHD), this study reviews literature data on pica, ADHD, and treatment response during childhood and adolescence and adds two case reports to this body of evidence. Methods: Systematic literature review using the key terms “pica”, “attention deficit”, “hyperactivity”, “child”, and “adolescent”. A retrospective analysis of clinical data of two patients with pica and ADHD followed at the Child and Adolescent Psychiatry Department of Hospital Pediátrico was also conducted. Results: As far as the authors are aware, only three cases are currently reported in the literature describing comorbid pica and ADHD in children. Of these, two reported complete pica symptom remission after methylphenidate treatment. Two other cases of children with pica and ADHD observed at the Child and Adolescent Psychiatry Department of our institution were reported in this study, one of which had complete symptom remission after psychostimulant treatment optimization. Discussion: The suggested association between pica and ADHD may have underlying etiology in poor impulse control and dopaminergic system dysfunctions. Therefore, a pharmacological approach capable of improving dopaminergic functioning may be an alternative treatment for pica. Psychostimulants may improve pica by eliciting an increase in brain dopamine levels and a decrease in impulsivity.